2019
DOI: 10.1186/s12876-018-0927-3
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infections in Ethiopia; prevalence and associated factors: a systematic review and meta-analysis

Abstract: BackgroundHelicobacter pylori (H.pylori) infections are prevalent and recognized as major cause of gastrointestinal diseases in Ethiopia. However, Studies conducted on the prevalence, risk factors and other clinical forms of H.pylori on different population and geographical areas are reporting conflicting results. Therefore, this review was conducted to estimate the pooled prevalence of H.pylori infections and associated factors in Ethiopia.MethodsPubMed, Embase, Google scholar, and Ethiopian Universities’ rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 72 publications
7
54
1
2
Order By: Relevance
“…6 A high overall pooled H pylori prevalence was identified (52.2%), although a trend of decreasing incidence was observed over time . 6 A high overall pooled H pylori prevalence was identified (52.2%), although a trend of decreasing incidence was observed over time .…”
Section: Ethiopiamentioning
confidence: 90%
See 2 more Smart Citations
“…6 A high overall pooled H pylori prevalence was identified (52.2%), although a trend of decreasing incidence was observed over time . 6 A high overall pooled H pylori prevalence was identified (52.2%), although a trend of decreasing incidence was observed over time .…”
Section: Ethiopiamentioning
confidence: 90%
“…A systemic review with meta-analysis of 37 studies, with a total of 18 890 participants, addressed H pylori prevalence and risk factors for infection in Ethiopia. 6 A high overall pooled H pylori prevalence was identified (52.2%), although a trend of decreasing incidence was observed over time . Low hygienic standards, alcohol consumption, and the presence of gastrointestinal symptoms were associated with a higher risk of infection.…”
Section: Ethiopiamentioning
confidence: 90%
See 1 more Smart Citation
“…Its global estimate was reported at 48.5% while continental reports were 69.4% in South America, 37.1% in North America, 24.4% in Oceania, 54.6% in Asia, 47.0% in Europe and 79.1% in Africa (7)(8)(9). In addition, the overall pooled prevalence of H.pylori infection in a systematic review and meta analysis study was 52.2%, and a sub-group analysis indicated that the highest prevalence was recorded from the Amhara National Regional State (54.6%) (10).…”
Section: Introductionmentioning
confidence: 98%
“…The trend of H.pylori infection showed a decreasing pattern in the last three decades from 1990 to 2017; 64.4% in the rst decade (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000), 62.2% in the second decade (2001-2011) and 42.9% in the third decade (2012-2017). This decrement might be related with relative improvements in sanitation, water access, life style and behavioral changes, quality of life and socioeconomic status, and increased awareness on the transmission, diagnosis, eradication therapy, prevention and control of H.pylori infection (10).…”
Section: Introductionmentioning
confidence: 99%